Students’ Challenges in Speaking English (A Case Study in the IPIREL of Universitas Muhammadiyah Yogyakarta) - Jaya, Patria Handung; Ananda Putri Salsabila; Dario Rifki Ismail; Paradita, Lanoke Intan (Ahmad Dahlan Journal of English Studies, 2025)
Speaking English is one of the most important skills in learning, especially as international class students. They need more effort to speak English correctly because they are required to use English in a daily basis in the learning process. However, this is the biggest challenge for them since English as a foreign language in Indonesia. While many researches mainly talk about speaking difficulty for students in general, this study aims to find out students' challenges in speaking English during class experienced by students in the international class program. In addition, because this research is a quantitative study, questionnaires were distributed to find out all the problems faced by International Program of International Relations (IPIREL) students in Universitas Muhammadiyah Yogyakarta (UMY). The results show that the challenges faced by students in speaking is the fear of making mistakes and the lack of vocabularies that limit them to produce the utterances, especially in the classroom. In facing the challenges, the students also have some strategies in handling the situation. It is expected that this research is able to make other students more aware of the possible challenges that they may face in speaking English and find some strategies to handle them.